2019
DOI: 10.14748/ssm.v51i1.5911
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sensitive skin on quality of life

Abstract: INTRODUCTION: Sensitive Skin Syndrome (SSS) is officially defined as a syndrome with unpleasant sensations like itching, pain, and numbness in response to stimuli that usually do not cause such sensations. In most of the cases it is a self-defined condition without objective pathological findings. Few studies have underlined the influence of SSS on the quality of life (QoL). The main problem is that people with sensitive skin suffer both with and without topical or internal care, which puts them in an extremel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Symptoms related to sensitive skin may adversely affect quality of life 21 . We observed that DLQI values increased and EUROHIS score decreased as skin sensitivity increased.…”
Section: Discussionmentioning
confidence: 66%
“…Symptoms related to sensitive skin may adversely affect quality of life 21 . We observed that DLQI values increased and EUROHIS score decreased as skin sensitivity increased.…”
Section: Discussionmentioning
confidence: 66%